2022
DOI: 10.1364/ol.471088
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient green emission Cs4PbBr6 quantum dots with stable water endurance

Abstract: To date, quantum dots (QDs) based on perovskite materials with high photoluminescence quantum yield (PLQY) and stability have rarely been reported. In this work, Cs4PbBr6 QDs glass ceramic with high PLQY and water stability is obtained, and the research results confirm that the strong green emission originates from the trapping of free excitons by internal Br vacancies. The rise of Br vacancies and the spontaneous growth of multi-morphology Cs4PbBr6 QDs under the influence of air humidity increase the PLQY to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…The use of GA ions has been reported to passivate defects in the perovskite systems, which can reduce non-radiative recombinations. 41,43,68 The steric suppression of phase segregation can stabilize the bandgap under illumination, 69 which is an indicator that the phase separation observed in the XRD results does not impact the bandgap model in a mixed GA and MA system. GA can serve as a modifying agent within the perovskite structure by inuencing phase stability and ion migration by various mechanisms.…”
Section: Discussionmentioning
confidence: 98%
“…The use of GA ions has been reported to passivate defects in the perovskite systems, which can reduce non-radiative recombinations. 41,43,68 The steric suppression of phase segregation can stabilize the bandgap under illumination, 69 which is an indicator that the phase separation observed in the XRD results does not impact the bandgap model in a mixed GA and MA system. GA can serve as a modifying agent within the perovskite structure by inuencing phase stability and ion migration by various mechanisms.…”
Section: Discussionmentioning
confidence: 98%
“…In fact, it has been reported that both the intact CsPbBr3 PNCs and Cs4PbBr6 NCs where CsPbBr3 PNCs are residually doped can emit green PL over 500 nm. 23,24,30,31,42,43 Therefore, the emergence of Cs-rich Cs4PbBr6 NPs is essentially not distinguishable by sole judgement from the PL peak positions. However, the colorless dispersions in the well plate suggest the phase transformation to Cs4PbBr6 NCs (Figure S2).…”
Section: Discussionmentioning
confidence: 99%